The fact-checking dilemma: Fact-checking increases the reputation of the fact-checker but creates perceptions of ideological bias - Aruguete, Natalia (2025)
This study examines how exposure to counter- and pro-attitudinal fact-checking messages impacts the fact-checker’s perceived quality and ideological leaning. In a well-powered and pre-registered survey experiment conducted during the 2021 mid-term election in Argentina, when COVID-19 was a polarizing issue, we exposed 5757 respondents to real tweets reporting the number of COVID-19 cases, followed by fact-checking adjudications that appropriately confirmed or refuted the original publication. Results show that pro-attitudinal messages increased the quality rating of the fact-checker, Chequeado, and made respondents perceive the organization ideologically closer to their views. Counter- attitudinal fact-checking also increases the perceived quality but has no significant effect on the perceived ideology of the fact-checker. Fact-checks are reputation-improving and do not seem to backfire. However, the intervention affects how voters perceive the ideological leaning of fact-checking organizations.